Chapter New perspectives for the quality of sub-municipal data with the Italian permanent population and housing census - Daddi, Stefano (Proceedings e report, 2023)
Over the years, official statistics have shown increasing attention to the territory in providing detailed and quality information and, in this sense, the Population and Housing Census has always guaranteed the availability of sub-municipal data useful for decision-making processes in the social, economic and environmental fields. The Istat modernization programme introduced the Permanent Census that, differently from the traditional decennial census essentially drew on collecting data from people, is strongly based on the integration of administrative and sample data, and planned for providing yearly statistical figures. This change requires new methodological and IT architectures. It is a revolution that - on the medium term - is expected to provide more stable and coherent figures at various territorial levels.In this framework, sub-municipal data derives from the integration of the Basic Register of Individuals and the Basic Register of Places. The quality of data depends on the quality of the Registers and the procedures adopted to integrate and elaborate input data. In this regard, Istat is working to improve the geocoding information and linkage procedures. One of the problem encountered is that of non-geocoded units. These are units without an allocation into an enumeration area because of problems in administrative data. Istat has studied a procedure integrating deterministic and probabilistic approaches for assigning the enumeration area to those critical units. An experimental study is carried out to evaluate the quality of the imputation procedure. In this paper, we discuss the approach adopted, the evaluation process, the results obtained and the impact on the quality of the data and the spatial analyses that can be carried out.